Efficacy and Safety of a Newly Developed Botulinum Toxin A (MBA-P01) in Patients with Moderate-to-Severe Glabellar Lines: A Randomized, Double-Blind, Active-Controlled, Multi-Center, Phase III Study with a Subgroup Analysis on Patients with COVID-19 - Hye Sung Han; Won-Serk Kim; Yangwon Lee; Chong-Hyun Won; Wooshun Lee; Sun Young Choi; Beom Joon Kim (Toxins)
MBA-P01 is a newly developed botulinum toxin A (BoNT-A) product designed to provide similar clinical effects as OnabotulinumtoxinA (ONA-BoNT-A), thereby providing an alternative treatment option for glabellar lines. It is another holotoxin preparation containing BoNT-A1. This randomized, double-blind, active-controlled, multi-center, Phase III clinical trial aimed to evaluate the efficacy and safety of MBA-P01 compared with OnabotulinumtoxinA (ONA-BoNT-A). In total, 318 participants were enrolled and received 20 units of MBA-P01 or ONA-BoNT-A on the forehead and glabella. At the 4-week assessment, the primary endpoint revealed no significant difference in the improvement rate of glabellar wrinkles between the two groups, confirming the non-inferiority of MBA-P01 to ONA-BoNT-A. Furthermore, some evaluation variables showed higher improvement rates for MBA-P01 than for ONA-BoNT-A. Adverse reactions and other safety analysis results were considered acceptable. Interestingly, a subgroup analysis of patients with the coronavirus disease (COVID-19) showed that the duration of BoNT-A treatment was shorter among those who contracted COVID-19 after BoNT-A treatment compared with those who have not. The limitations of this study include the predominance of female participants and the exclusive enrollment of Korean patients. MBA-P01 is expected to be clinically useful in terms of the efficient and safe reduction of glabellar wrinkles, which will provide patients with additional treatment options.